Biochar and Sulphur Enriched Digestate: Utilization of Agriculture Associated Waste Products for Improved Soil Carbon and Nitrogen Content, Microbial Activity, and Plant Growth - Tereza Hammerschmiedt; Jiri Holatko; Marek Sudoma; Antonin Kintl; Jan Vopravil; Pavel Ryant; Petr Skarpa; Maja Radziemska; Oldrich Latal; Martin Brtnicky (Agronomy, 2021)
A number of agriculture residues may be used either directly or after suitable treatment as amendments to improve soil quality. Such materials include biochar made of agriculture residues, digestate or elemental sulphur obtained from biogas desulphurisation. The joint use of these materials via pre-incubation may be more advantageous than only mixing prior the application to soil. In this study, digestates were mixed with amendments and incubated for 6 weeks before application to soil in a short-term pot experiment with lettuce (Lactuca sativa). The following treatments were tested: control digestate, digestate + biochar, digestate + elemental sulphur, digestate + biochar + elemental sulphur. The biochar-enriched digestate significantly increased soil microbial biomass, soil C:N, fresh above ground biomass, fresh and dry root biomass. Elemental sulphur-enriched digestate caused highest arylsulfatase and phosphatase, increased urease, microbial biomass in soil and fresh root biomass. Amendment of digestate + biochar + sulphur led to the significantly highest total soil carbon, microbial biomass, β-glucosidase, urease, and increased C:N ratio, arylsulfatase in soil and root biomass. It mitigated the adverse effect of either biochar or elemental sulphur on soil respiration. Properties of digestates were apparently affected by pre-incubation. This approach in digestate fertilizer production may contribute to sustainable farming.